The Implementation of Teaching Materials Reading Graphic Organizers in Elementary Schools - Otang Kurniaman; Cici Oktari; Pahrurazi Pahrurazi (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2019)
Reading is a very important skill that must be mastered by elementary school students, in the implementation of learning the teacher also provides a large contribution so that it is required to be able to develop teaching materials as a professional requirement. This research is a classroom action research using graphic organizer teaching materials in reading in the fourth grade of SDN 38 Pekanbaru with a total of 24 students. Before the implementation of learning in advance the implementation plan of learning was validated by several experts and practitioners with the results of the identity aspect validation obtained an average of 87 with a very decent category, and the assessment aspect obtained an average of 98 with a very decent feasible category. The results of the implementation of teacher activities in cycle I have obtained an average of 79% at meeting 1, meeting 2 obtained an average of 83%, meeting 3 obtained an average of 88% and meeting 4 obtained an average of 92%. The results of the research activities of meeting 1 student have obtained an average of 75%, meeting 2 was obtained an average of 79%, meeting 3 was obtained an average of 83%, and meeting 4 obtained an average of 88%. The results of the assessment of reading comprehension with the use of graphic organizer teaching materials from a base score of 42.50, the first cycle obtained an average of 71.88, the second cycle obtained an average of 76.88, with an increase from the base score to the first cycle obtained by 29, 38% while from the basic score to the second cycle obtained an average of 34.38%. The results of this study prove that the implementation of teaching materials to read the graphic organizer is able to improve reading comprehension skills.